Copper(II) ion-exchanged montmorillonite as catalyst for the direct addition of N-H bond to CC triple bond - Joseph, Trissa; Shanbhag, G. V.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A - Chemical, 2005)
An efficient synthesis of phenyl-(1-phenylethylidene)amine using copper-exchanged montmorillonite clay (Cu K-10) is demonstrated. The catalyst was characterized using UV-vis, XRD, BET surface area measurements, pyridine adsorption etc. The XRD and surface area measurement show that the structural characteristics of the support montmorillonite K-10 (K-10) are preserved after Cu exchange. The hydroamination of phenyl acetylene with aniline was carried out in toluene under reflux condition in N-2 atmosphere at 393 K. The reaction is highly regio-selective for only Markovnikoff's addition of an-tine to CC multiple bond and proceeded smoothly to completion. The reaction conditions were optimized to obtain complete conversion with respect to phenyl acetylene. Reaction data showed that the activity of the catalyst in hydroamination reaction is greater at higher reaction temperatures and nonpolar solvents and NZ pressure promotes the reaction drastically. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: alkyne; Aniline; Catalyst; hydroamination; K-10 montmorillonite clay; phenyl acetylene

Silicotungstate-modified zirconia as an efficient catalyst for phenol tert-butylation - Devassy, Biju M.; Shanbhag, G. V.; Mirajkar, Subhash P.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2005)
The alkylation of phenol with tert-butanol was investigated using zirconia modified with silicotungstic acid (STA) as catalysts. The catalysts with different STA loading (5-25 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 350 to 850 degrees C) were prepared and characterized by X-ray diffraction and NH3-TPD measurements. The XRD results indicate that STA stabilizes the tetragonal phase of zirconia. The catalyst with 15% STA on ZrO2 calcined at 750 degrees C shows the highest acidity and hence highest activity. Under the reaction conditions of 140 degrees C, tert-butanol/phenol molar ratio of 2 and LHSV of 4 h(-1), phenol conversion was 95.4% with selectivity to 2-tert-butyl phenol 4.3%, 4-tert-butyl phenol 59.2% and 2,4-di-tert-butyl phenol 35.8%. The reaction was studied as a function of time for 50 It without appreciable change in phenol conversion and product selectivity. The deactivated catalyst could be regenerated by calcination with out appreciable lose in catalytic activity and product selectivity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: phenol; Silicotungstic acid; tert-butylation; Zirconia

Zirconia-supported phosphotungstic acid as catalyst for alkylation of phenol with benzyl alcohol - Devassy, Biju M.; Shanbhag, G. V.; Lefebvre, F.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The liquid-phase alkylation of phenol with benzyl alcohol was carried out using zirconia-supported phosphotungstic acid (PTA) as catalyst. The catalysts with different PTA loadings (5-20 wt.% calcined at 750 degrees C) and calcination temperature (15 wt.% calcined from 650 to 850 degrees C) were prepared and characterized by (31)p MAS NMR and FT-IR pyridine adsorption spectroscopy. The catalyst with optimum PTA loading (15%) and calcination temperature (750 degrees C) was prepared in different solvents. 31p MAS NMR spectra of the catalysts showed two types of phosphorous species, one is the Keggin unit and the other is the decomposition product of PTA and the relative amount of each depends on PTA loading, calcination temperature and the solvent used for the catalyst preparation. The catalysts with 15% PTA on zirconia calcined at 750 degrees C showed the highest Bronsted acidity. At 130 degrees C and phenol/benzyl alcohol molar ratio of 2 (time, I h), the most active catalyst, 15% PTA calcined at 750 degrees C gave 98% benzyl alcohol conversion with 83% benzyl phenol selectivity. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Benzylation; phenol; Phosphotungstic acid; Zirconia

Chemoselective anti-Markovnikov hydroamination of alpha,beta-ethylenic compounds with amines using montmorillonite clay - Joseph, Trissa; Shanbhag, G. V.; Sawant, D. P.; Halligudi, Shivappa B. (Journal of Molecular Catalysis A-Chemical, 2006)
The catalytic activity of montmorillonite clays as a catalyst for the hydroamination of alpha,beta-ethylenic compounds with amines was tested. Aniline and substituted amines reacted with alpha,beta-ethylenic compounds in the presence of catalytic amount of commercially available clay to afford exclusively anti-Markovnikov adduct in excellent yields. Aniline reacted with ethyl acrylate to yield only anti-Markovnikov adduct N-[2-(ethoxycarbonyl)ethyl] aniline (mono-addition product). No Markovnikov adduct (N-[1-(ethoxycarbonyl)ethyl]aniline and double addition product N,N-bis[2-(ethoxycarbonyl)ethyl]aniline were formed under selected reaction conditions. For a better exploitation of the catalytic activity in terms of increased activity and improved selectivity for the mono-addition product, the reaction parameters were optimized in terms of temperature, solvent, reactant mole ratio. Under optimized reaction conditions, montmorillonite clay K-10 showed a superior catalytic performance in the hydroamination of ethyl acrylate with aniline with a conversion of aniline to mono-addition product (almost 100% chemoselectivity) with a high rate constant 0.3414 min(-1) compared to the reported protocols. The dependence of conversion of aniline over different types of montmorillonite clays (K-10, K-20, K-30, Al-Pillared clay and untreated clay) has also been discussed. The activities of clay for the hydroamination of different aromatic and aliphatic amines have also been investigated. Under harsh reaction conditions (increased temperature and long reaction time) small amounts of di-addition products were observed. The kinetics data has been interpreted using the initial rate approach model. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alpha; amines; anti-Markovnikov addition product; beta-ethylenic compounds; chemo-selective; hydroamination; K-10 montmorillonite clay

Heteropoly acid supported on titania as solid acid catalyst in alkylation of p-cresol with tert-butanol - Kumbar, Suresh M.; Shanbhag, G. V.; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
Butylation of p-cresol with tert-butanol was investigated on titania modified with 12-tungstophosphoric acid (TPA/TiO2) catalyst under vapor phase conditions. Catalysts with different TPA loadings (10-25 wt.%) and calcination temperatures (650-750 degrees C) were prepared by suspending titanium hydroxide in methanol solution of TPA followed by drying and calcination. These catalysts were characterized by surface area, XRD, P-31 MAS NMR, XPS, NH3-TPD, and FTIR pyridine adsorption. XRD results indicated that the presence of TPA retarded the crystallization of titania and stabilized TiO2 in anatase phase. P-31 MAS NMR indicated the presence of TPA in various forms (dispersed, highly fragmented and Keggin intact). These catalysts showed both Bronsted and Lewis acidity, and 20% TPA on TiO2 calcined at 700 degrees C (from here after words 20% TT 700) had the highest Bronsted as well as total acidity. Further, the catalytic activities were examined in tert-butylation of p-cresol with tent-butanol. The catalytic activity depended on TPA coverage, and the highest activity corresponded to the monolayer of TPA on titania. The most active catalyst 20% TT-700 gave 82% conversion of p-cresol and 89.5% selectivity towards 2-tert-butyl cresol (TBC), 2,6-di-tert-butyl cresol (DTBC) 7.5% and cresol-tert-butyl ether (CTBE) 3% under optimized conditions. The activity was always higher than that of WO3/ZrO2, sulfated zirconia (SZ), USY, H-beta zeolites and montmorillonite K-10 (K-10mont) under similar conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: 2; 2-tert-butyl-p-cresol; 6-di-tert-butyl-p-cresol; Alkylation; heteropoly acid; p-Cresol; tert-butanol; titania

Non-phosgene route for the synthesis of methyl phenyl carbamate using ordered AISBA-15 catalyst - Lucas, Nishita; Amrute, Amol P.; Palraj, K.; Shanbhag, G. V.; Vinu, Ajayan; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
Methyl phenyl carbamate (MPC) has been synthesized Under liquid phase conditions from dimethyl carbonate and aniline by using mesoporous AISBA-15 catalyst. The catalyst with different Si/Al ratio was synthesized by isomorphous Substitution of aluminium into the framework of siliceous SBA-15. The structural integrity of the catalyst system was diagnosed with the help of various characterization techniques Such as X-ray diffraction, Surface analysis, and the acidity measurement has been done by TPD using ammonia as probe molecule. AISBA-15 (Si/Al = 10) exhibited highest catalytic activity in the synthesis of MPC under the reaction Conditions Studied. The effect of parameters Such as molar ratio of reactants, catalyst concentration. reaction temperature and time on the conversion of aniline was investigated. The results demonstrated that an aniline conversion of 99% and MPC selectivity of 71% were achieved when the reaction was carried out at 100 C, DMC to aniline mole ratio of 10 with 5% of catalyst (wt% of total reaction mixture) for 3 h. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: amines; Dimethyl carbonate; Mesoporous AISBA-15; Methoxycarbonylation; Methyl phenyl carbamate